(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Events Of May 8, 1945, Were A Positive Turning Point In The History Of The National Movement In General And The People’s Party In Particular. Like The Great Actions And Profound Transformations In The Lives Of Peoples, They Were Sudden In Their Eruption, Limited In Their Geographical Scope And Time, But Serious In Their Far-Reaching Consequences In The Developments That It Resulted In It, Which Made It In The Memory Of History, Paved A New Era And The Beginning Of A Timeless Epic In Algerian History Was The Conqueror Of November 1954, The Culmination Of It, And The Historical Writings Consider That The Events Of The Eighth Of May 1945 AD As The First Spark Of The Start Of The Liberation Revolution, Has Awakened These Massacres Now The Algerian People Are Sure That What Was Taken By Force Is Only Recovered, And Among The Writers Who Contributed To The Clarification Of The Events Of 8 May, We Mention: Rabie Bouchama, Aziz Bin Omar, Mohammed Eid Al Khalifa, Mohamed Bouzouaoui, Hamza Boukoucha ... And Other Writers, However, The First Initiative Was By Mohamed Bashir Brahimi, Who Wrote A Single Article On The Occasion Of The Third Anniversary Of The Massacres On 10 May 1948 Entitled The Anniversary Of 8 May, And Organized Poetry Expressive On The Occasion Of The Fifth Anniversary And Published On 15 May 1950 In Al-Basair Newspaper. Key Words- The Massacres Of 08 May 1945, Mohamed Bashir Brahimi, Historical Writing, Demonstrations 08 May 1945, The Writings Of Bashir Brahimi. Poems Of Bashir Brahimi.